PENERAPAN TANGGUNG JAWAB PELAKU USAHA PENJUAL MAKANAN KEMASAN YANG TELAH DALUARSA TERHADAP KONSUMEN DI KOTA PEKANBARU - Reski Hidayat; Firdaus Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Packaged food is often a tool for business crime, for example, selling expired packaged food that contains ingredients that are harmful to health, packaged food is neatly packaged, clean and has an expiration date for sale within an estimated timeframe. One form of business crime committed by some irresponsible entrepreneurs is to produce, distribute, and offer products that are harmful to human health (consumers). The act of the businessmen only concerned with profits without paying attention to the consequences for these consumers have claimed many victims. Global competition that occurs makes producers justify any means to reap profits. As a result, various methods are used to trick consumers.The problem that the author makes the basis of this research is what is the form of legal protection for consumers of food in expired packaging and how is the responsibility of business actors in the event of a dispute between consumers and business actors for food in expired packaging. The purpose of this research is to find out the legal protection for consumers of expired packaged food and to find out the solution if consumers' rights are not fulfilled by business actors and as input for all parties related to the problem being examined. This type of research can be classified into empirical or sociological research types, because in this study the author directly conducts research at the location or place of study in order to provide a complete and clear picture of the problem under study.This research was conducted at the Pekanbaru City Food and Drug Supervisory Agency, the data sources used were primary and secondary data, data collection techniques in this study with questionnaires, interviews and literature review. The results of this study are first. legal protection for consumers has been protected by Law No. 8 of 1999 concerning Consumer Protection, producers often neglect consumer protection, in maintaining legal protection for consumers the government also participates in maintaining legal protection for consumers by providing administrative sanctions and providing fines to business actors who do not carry out their obligations to protect consumers, secondly, in the case of business actors' responsibility towards consumer protection in Article 7 of Law Number 8 of 1999 concerning Consumer Protection, namely by making compensation to consumers who have lost product sold by these business actors, besides that the government also contributes in terms of providing responsibility for consumer protection by supervising business actors who ignore consumer protection.Keywords: Consumers, Packaged Foods, Expiration